Science-Economy-Technology Concordance Matrix for Development and Implementation of Regional Smart Specializations in the Silesian Voivodeship, Poland - Adam Smoliński; Jan Bondaruk; Magdalena Pichlak; Leszek Trząski; Elżbieta Uszok (The Scientific World Journal)
The regional smart specializations include the innovative activities within a common science-economy-technology sector, which open the opportunities to gain a competitive advantage. The original procedure of science-economy-technology concordance matrix development on an example of smart specializations of the Silesian Voivodeship was presented in the paper. The procedure developed includes recognition of the research and economic components of the regional smart specialization and the connection between the economic components of the regional specialization and the technological innovation through the international patent classification. It also comprises recognition of key enabling technologies (KETs) and high technologies (of high R&D intensity) other than KET in the economic and technological dimensions of innovation as well as the high R&D intensity services in the economic dimension of innovation. The in-depth expert analyses with the application of the Delphi method were also taken into account. The methodological approach developed and the visualization method applied are both of cognitive and practical importance since they contribute significantly to the creation of efficient development policies, to the enhancement and facilitation of cross-sectoral cooperation, and to the focusing on the fields of key importance in terms of the competitive advantage of a region.